Características epidemiológicas dos óbitos fetais e neonatais precoces de filhos de pacientes com near mis - Nardello, Daniele Marin (2016)
Objective: To identify the epidemiological characteristics of early fetal and neonatal deaths in maternal near miss patients and the associated elements to this outcome. Method: Cross-sectional study including 79 women with features near miss, identified in a one-year period, and their newborns. Semi-structured interviews and the study of patients’ records were conducted. The variables were analyzed through simple frequency and percentage. To evaluate the association between those variables, the Fisher’s Exact Test was used. For the multivariate analysis the perceptual map constructed from the multiple correspondence examination was used, using the variables that were significant to 20%. Results: Amongst the near miss mothers, hypertensive disorders (severe pre-eclampsia, eclampsia, hypertension) totalized 32 cases (40,5%) and, of those, 14 (58,3%) had fetal and neonatal adverse outcome (p 0,046). The highest prevalence of fetal and neonatal adverse outcome was derived from cesarean delivery (20, 83,3%), of women with 2 or 3 children (11, 45,8%), and without previous stillbirths (17, 70,8%), this last variable with significance p 0,038. In the fetal and neonatal adverse outcome analysis significant levels were verified in newborns admitted in Neonatal Intensive Care Unit (17, 70,8%, p < 0,001); children with gestational age < 32 weeks (10, 41,6%, p < 0,001); birth weight < 2500 (16, 66,7%, p 0,001); APGAR score at 5 minutes < 7 (9, 52,9%, p < 0,001); neonatal asphyxia, 9 (50,00%, p < 0,001); and early respiratory distress syndrome, 13 (72,2%, p 0,002). Conclusion: The characteristic of early fetal and neonatal deaths in maternal near miss patients had a close association with fetal and neonatal adverse outcome. Among the mothers with hypertensive disorders the significant characteristics to the outcome in newborns were prematurity, neonatal asphyxia and early respiratory distress syndrome.